Reading motivation of students in a secondary school in rural area of Johor [electronic resource] - Nurliyana Ismail, 1986- (2012)
Thesis (Sarjana Pendidikan (Pengajaran Bahasa Inggeris sebagai Bahasa Kedua)) - Universiti Teknologi Malaysia,2012